The Mediating Effects of Governance, Financial Literacy, and Technological Innovation on Digital Finance in North Sumatra’s Rural Banks - Petrus Loo (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The rapid shift to digital financial systems has transformed rural banking, yet challenges like uneven adoption and limited financial literacy persist in regions like North Sumatra. This study aims to examine how financial inclusion and taxation influence digital finance adoption in North Sumatra’s rural banks, focusing on the mediating roles of corporate governance, financial literacy, and technological innovation. Using a quantitative approach with Structural Equation Modeling, data were collected from 91 rural banks through questionnaires, documentation, and observations. The findings confirm that financial inclusion and taxation significantly drive digital finance, both directly (p<0.05) and through the mediators, with corporate governance, financial literacy, and technological innovation explaining 85.4% of the variance in digital finance adoption. These results highlight the critical role of inclusive financial systems and transparent tax policies in enhancing digital transformation. The study concludes that rural banks should prioritize financial literacy programs and digital tax systems to improve efficiency, particularly in less-developed districts like Nias. These findings offer practical strategies for rural banks and policymakers to strengthen digital financial systems and promote inclusive growth in North Sumatra.